Katekese Keluarga pada Masa Pandemi Covid 19 dalam Perspektif Model Katekese Ritual Maggid - Agustinus Mujianto; Antonius Denny Firmanto (Institut Filsafat dan Teknologi Kreatif Ledalero, 2021)
This paper aims to provide new insights on the importance of family catechesis during the Covid 19 pandemic. During the Covid 19 pandemic, religious activities have been eliminated or restricted. Normally, Catholics can celebrate worship at church, but that will no longer be possible after the government prohibits gathering to prevent the transmission of the Coronavirus. Therefore, this situation hinders the formation of the faith of the people. Then, there was a shift in the celebration of faith which was originally held in the church to be carried out in the family during the Covid 19 pandemic. Therefore, family catechesis in this regard plays an important role in the celebration of faith within the family itself. The methodology is a qualitative method. The data were collected from books, news, and journals. For data analysis, this study used a deductive method with maggid ritual catechesis model as a perspective. This study found that family catechesis with the maggid ritual catechesis model can answer what the Catholic family missed during the Covid 19 pandemic, namely the celebration of togetherness, the experience of community faith, internalization, and transformation. Key words: Catechesis, Faith Celebration, Family, Maggid Ritual